2020
DOI: 10.1002/ecy.3027
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term photo‐id and satellite tracking reveal sex‐biased survival linked to movements in an endangered species

Abstract: GC (2020). Long-term photo-id and satellite tracking reveal sex-biased survival linked to movements in an endangered species. Ecology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 59 publications
(103 reference statements)
1
47
0
Order By: Relevance
“…Direct counts of turtles using unmanned autonomous vehicles indicated the presence of up to 90 unique males and 240 unique females in the breeding area in one season (Schofield et al, 2017), falling within the range predicted for previous years based on nest counts by Schofield et al (2015). Tracking of male and female sea turtles from Zakynthos (n = 20 females, Zbinden et al, 2011; n = 55 males and females, Schofield et al, 2020) has demonstrated that females migrate to other areas of the Mediterranean following breeding, whereas around 30% of males remain resident. This information has been corroborated with longterm photo-identification records of over 1000 unique adult male and females, as well as immature turtles (Schofield et al, 2008(Schofield et al, , 2020.…”
Section: Study Site and Speciesmentioning
confidence: 78%
See 1 more Smart Citation
“…Direct counts of turtles using unmanned autonomous vehicles indicated the presence of up to 90 unique males and 240 unique females in the breeding area in one season (Schofield et al, 2017), falling within the range predicted for previous years based on nest counts by Schofield et al (2015). Tracking of male and female sea turtles from Zakynthos (n = 20 females, Zbinden et al, 2011; n = 55 males and females, Schofield et al, 2020) has demonstrated that females migrate to other areas of the Mediterranean following breeding, whereas around 30% of males remain resident. This information has been corroborated with longterm photo-identification records of over 1000 unique adult male and females, as well as immature turtles (Schofield et al, 2008(Schofield et al, , 2020.…”
Section: Study Site and Speciesmentioning
confidence: 78%
“…The loggerhead sea turtle population of the Mediterranean is currently listed in the category of Least Concern in the International Union for Conservation of Nature (IUCN) Red List of Threatened Species (IUCN, 2020), with its current status considered conservation dependent, as a result of long-term conservation efforts (Casale, 2015). Adult turtles migrate into Laganas Bay to mate as early as March, with most adult males departing in late May, whereas females typically remain to nest from mid-May to early August, at which point they depart for foraging grounds up to 1000 km away (Schofield et al, 2013(Schofield et al, , 2020. Direct counts of turtles using unmanned autonomous vehicles indicated the presence of up to 90 unique males and 240 unique females in the breeding area in one season (Schofield et al, 2017), falling within the range predicted for previous years based on nest counts by Schofield et al (2015).…”
Section: Study Site and Speciesmentioning
confidence: 99%
“…Using a combination of photo-identification and satellite tracking technology in the Mediterranean, Schofield et al . [ 35 ] found an annual mortality rate of 0.11 for female and 0.27 for male loggerheads. Bentivegna et al .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, whether there are sex-specific differential mortalities across age classes requires further investigation. For instance, male leatherback turtle Dermochelys coriacea hatchlings may exhibit higher fitness than females (Rivas et al 2019), while adult loggerhead females might exhibit higher annual survival rates than males (Schofield et al 2020).…”
Section: Reconstructing Past and Future Nest Temperaturementioning
confidence: 99%